Hydroxysafflor Yellow A Inhibits TNF-α-Induced Inflammation of Human Fetal Lung Fibroblasts via NF-κB Signaling Pathway. (26th December 2019) - Liu, Sen; Wang, Yan; Wen, Huijuan; Sun, Xiaofang; Wang, Yu
Abstract : Objective . Hydroxysafflor yellow A (HSYA), an effective ingredient of the Chinese herb Carthamus tinctorius L, attenuated bleomycin-induced pulmonary fibrosis in mice. This study is to investigate the effect of HSYA on the proliferation and inflammatory level of human fetal lung fibroblasts (MRC-5 cells) induced by tumor necrosis factor- α (TNF- α ) and explore the underlying mechanisms. Methods . MRC-5 cells were treated with different concentrations of TNF- α, HSYA, or/and etanercept (ENCP, TNF- α receptor (TNFR1) antagonist, 500 ng/mL) before cell proliferation was detected. The laser confocal microscope was used to observe the role of HSYA in binding of TNF- α and its receptor. Co-immunoprecipitation was used to detect the binding of TNFR1 and TAK1-TAB2 complex. Real-time quantitative RT-PCR and western blot were used to detect the expressions of inflammation-related cytokines and proteins related with the NF- κ B pathway. Luciferase reporter gene assay and chromatin coprecipitation method were used to detect the interaction between AP-1 and TGF- β 1 promoter. Results . TNF- α (5 ng/mL) was used to induce inflammation and proliferation in MRC-5 cells. HSYA can partially suppress the stimulation of TNF- α on proliferation and inflammatory response of MRC-5 cells. HSYA could compete with TNF- α to bind with TNFR1 and hamper the binding of TNFR1 to TAK1-TAB2 complex. In addition, HSYA could also inhibit the activation of the NF- κ B signal pathway and suppress the binding of TGF- β 1 promoter with AP-1. Conclusion . Evidence in this study suggested that HSYA affects TNF- α -induced proliferation and inflammatory response of MRC-5 cells through the NF- κ B/AP-1 signaling pathway, which may provide theoretical basis for HSYA treatment in pulmonary fibrosis.